CRITICISM IN COVID-19 RESPONSES AT VOLUNTEER ACCOUNT @PANDEMICTALKS (NORMAN FAIRCLOUGH'S CRITICAL DISCOURSE ANALYSIS MODEL) - Wijaya, Gustaf; Ida, Rachmah (The Journal of Society and Media, 2021)
The Covid-19 pandemic in Indonesia since March 2020 has tested the Indonesian government's capabilities in various aspects, including public health communication. The existence of communication media both from the Government and the mass media is considered insufficient in providing information related to Covid-19. The advancement of the internet and new media has made social media, especially Instagram, play a vital role in disseminating information related to Covid-19. The information gap that occurs encourages netizens to collaborate to fill it. One of the information volunteers regarding Covid-19 is the Instagram account @pandemictalks, with educational content and criticism of the handling of Covid -19 in Indonesia. This study captures how the discourse on the handling of Covid-19 was put forward by the volunteer account @pandemictalks. This study uses Norman Fairclough's Critical Discourse Analysis Model, this model dissects discourse not only from the linguistic aspect but also into the social aspect and the context involved in it. This study provides an overview of the various forms of criticism that @pandemictalks conveyed, their production and distribution, social changes that occurred, and related policy changes in them.